Effect of Oxytocin Massage on Breast Milk Production in Postpartum Mothers: A Case Study - Sandriani Sandriani; Rini Fitriani; Gumelar Zati Rahayu (Yayasan Inspirasi El Burhani, 2023)
Introductions: Oxytocin massage is one of the non-pharmacological ways that can be done so that milk production increases and runs smoothly. Oxytocin massage aims to stimulate the postpartum mother's oxytocin hormone, which is carried out on the head, neck, back, and along the spine. Aims: This study aims to describe care with oxytocin massage interventions to facilitate breastfeeding in postpartum patients. Methods: The research used is a descriptive approach through the nursing care process method which consists of the first assessment carried out by observing and interviewing patients to obtain data and information for data analysis, the second is establishing diagnoses that appear to clients after the data collection process, the third is intervention or planning actions that will be carried out, the fourth is the implementation, namely the implementation of the planned actions, and finally the evaluation by documenting the nursing care process from start to finish. The intervention was carried out in the inpatient room of the Banjar City Hospital for 1 postpartum person by giving oxytocin massage. Results: From the effects of the oxytocin massage intervention there was a change in milk production, and milk expenditure became more, whereas from the anamnesis results obtained subjective data, the client said it was difficult to express milk. Conclusions: Oxytocin massage can be a nursing intervention in promoting breastfeeding in postpartum mothers who are constrained about breastfeeding, with nursing diagnoses that breastfeeding is ineffective.